2005
DOI: 10.1192/bjp.186.3.209
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of syntax production in schizophrenia

Abstract: The absence of activation in the right posterior temporal and left superior frontal cortex in patients with schizophrenia might contribute to the articulation of grammatically more simple speech in people with this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 27 publications
(37 reference statements)
4
47
0
1
Order By: Relevance
“…So far cognitive neuroimaging research on language has focused on comprehension (Gernsbacher & Kashak, 2003), and the few studies on language production are mostly either on single word production (Alario, Chainay, Lehericy, & Cohen, 2006;Karbe, Herholz, Weber-Luxenburger, Ghaemi, & Heiss, 1998;Kircher, Brammer, Tous Andreu, Williams, & McGuire, 2001;Tremblay & Gracco, 2006;Tremblay & Gracco, 2010;Tremblay & Small, 2011b;Wise et al, 2001;Zheng, Munhall, & Johnsrude, 2010; for a review, see Indefrey & Levelt, 2004), or on covert production (den Ouden, Hoogduin, Stowe, & Bastiaanse, 2008). The neuroimaging studies that have investigated overt sentence-level production either treat sentence production as a unitary process (Awad, Warren, Scott, Turkheimer, & Wise, 2007;Blank, Scott, Murphy, Warburton, & Wise, 2002;Brownsett & Wise, 2010;Foki, Gartus, Gesissler, & Beisteiner, 2008;Kemeny, Ye, Birn, & Braun, 2005;Kircher, Brammer, Williams, & McGuire, 2000;Stephens, Silbert, & Hasson, 2010), or isolate only one component of speech production (Haller, Radue, Erb, Grodd, & Kircher, 2005;Indefrey et al, 2001;Kircher, Oh, Brammer, & McGuire, 2005;Tremblay & Small, 2011a). It is, therefore, unknown to what degree the different cognitive stages in speech production also recruit different neuronal networks.…”
Section: Introductionmentioning
confidence: 99%
“…So far cognitive neuroimaging research on language has focused on comprehension (Gernsbacher & Kashak, 2003), and the few studies on language production are mostly either on single word production (Alario, Chainay, Lehericy, & Cohen, 2006;Karbe, Herholz, Weber-Luxenburger, Ghaemi, & Heiss, 1998;Kircher, Brammer, Tous Andreu, Williams, & McGuire, 2001;Tremblay & Gracco, 2006;Tremblay & Gracco, 2010;Tremblay & Small, 2011b;Wise et al, 2001;Zheng, Munhall, & Johnsrude, 2010; for a review, see Indefrey & Levelt, 2004), or on covert production (den Ouden, Hoogduin, Stowe, & Bastiaanse, 2008). The neuroimaging studies that have investigated overt sentence-level production either treat sentence production as a unitary process (Awad, Warren, Scott, Turkheimer, & Wise, 2007;Blank, Scott, Murphy, Warburton, & Wise, 2002;Brownsett & Wise, 2010;Foki, Gartus, Gesissler, & Beisteiner, 2008;Kemeny, Ye, Birn, & Braun, 2005;Kircher, Brammer, Williams, & McGuire, 2000;Stephens, Silbert, & Hasson, 2010), or isolate only one component of speech production (Haller, Radue, Erb, Grodd, & Kircher, 2005;Indefrey et al, 2001;Kircher, Oh, Brammer, & McGuire, 2005;Tremblay & Small, 2011a). It is, therefore, unknown to what degree the different cognitive stages in speech production also recruit different neuronal networks.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroimaging studies investigating the neural basis of these symptoms in schizophrenic adults have regularly identified both abnormal structural organization in language-related circuitry (DeLisi, Szulc, Bertisch, Majcher & Brown, 2006; Walder et al, 2007; Weiss, Dewitt, Goff, Ditman & Heckers, 2005) and aberrant patterns of neural activity in fronto-temporal networks in response to a broad range of tasks with linguistic demands (Kircher, Oh, Brammer & McGuire, 2005; Kuperberg, Deckersbach, Holt, Goff & West, 2007; Kuperberg, West, Lakshmanan & Goff, 2008; Ngan et al, 2003; Ragland et al, 2008; Razafimandimby et al, 2007; Weinstein, Werker, Vouloumanos, Woodward & Ngan, 2006; Weiss et al, 2006). For example, research has found that schizophrenic adults exhibit abnormal neural activity as compared to normal adults when assessing word meaning, with hypoactivation in some frontal regions and hyperactivation in others (Kubicki et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Crow et al, 1995;DeLisi et al, 1991). Recent fMRI studies provoking activation with a language production paradigm in patients who already have the diagnosis of acute or chronic schizophrenia (Boksman et al, 2005;Kircher et al, 2001Kircher et al, , 2005Koeda et al, 2006;Kubicki et al, 2003;Sommer et al, 2001Sommer et al, , 2003Weiss et al, 2006) and in those during the prodromal stage prior to illness onset and/or at high-genetic risk for illness (Whalley et al, 2004(Whalley et al, , 2005(Whalley et al, , 2006 have shown disruption in the normal lateralized activation in the frontal and temporal cortical circuits for language processing and further evidence that this pattern is heritable (Sommer et al, 2004). Other studies, mostly focusing on activation during tasks engaging working memory (Callicott et al, 2003;Keshavan et al, 2002;Seidman et al, 2006;Thermenos et al, 2004), attentional processes (Morey et al, 2005) in the prefrontal cortex, or facial expression and amygdala response (Habel et al, 2004), have suggested that these functional changes also occur early on and could be vulnerability markers for the illness.…”
Section: Introductionmentioning
confidence: 99%